Plasma glucose kinetics during prolonged exercise in trained humans when fed carbohydrate - Angus, D. J.; Febbraio, M. A.; Hargreaves, M. (American Journal of Physiology, Endocrinology and Metabolism, 2002)
Nine endurance-trained men exercised on a cycle ergometer at ~68% peak O2 uptake to the point of volitional fatigue [232 ± 14 (SE) min] while ingesting an 8% carbohydrate solution to determine how high glucose disposal could increase under physiological conditions. Plasma glucose kinetics were measured using a primed, continuous infusion of [6,6-2H]glucose and the appearance of ingested glucose, assessed from [3-3H]glucose that had been added to the carbohydrate drink. Plasma glucose was increased (P < 0.05) after 30 min of exercise but thereafter remained at the preexercise level. Glucose appearance rate (Ra) increased throughout exercise, reaching its peak value of 118 ± 7 µmol · kg1 · min1 at fatigue, whereas gut Ra increased continuously during exercise, peaking at 105 ± 10 µmol · kg1 · min1 at the point of fatigue. In contrast, liver glucose output never rose above resting levels at any time during exercise. Glucose disposal (Rd) increased throughout exercise, reaching a peak value of 118 ± 7 µmol · kg1 · min1 at fatigue. If we assume 95% oxidation of glucose Rd, estimated exogenous glucose oxidation at fatigue was 1.36 ± 0.08 g/min. The results of this study demonstrate that glucose uptake increases continuously during prolonged, strenuous exercise when carbohydrate is ingested and does not appear to limit exercise performance.